THE OMBUDSMAN AS AN INTERMEDIARY BETWEEN THE STATE AND THE CITIZEN: MECHANISMS FOR RESTORING VIOLATED RIGHTS (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2026)
The article examines the role of the Ombudsman institution as a key intermediary between the state and the citizen in the mechanism of restoration of violated rights. The article reveals the legal nature of the Ombudsman as an independent human rights institution operating on the basis of the constitutional principles of the rule of law, justice and the priority of human rights. Special attention is paid to procedures for reviewing citizens’ appeals, ensuring accessibility and prompt protection of rights, as well as analyzing the practice of restoring violated rights using the example of interaction with government agencies and the judicial system.Based on the analysis of statistics of appeals and law enforcement practice, it is shown that the institution of the Ombudsman helps to increase citizens’ trust in state institutions and strengthen the principle of a «listening state». The mechanisms for implementing the recommendations of the Ombudsman, their impact on improving legislation and administrative practice, as well as the problems of implementing response acts related to the lack of binding force of recommendations and insufficient coordination between authorities are considered.It is concluded that there is a need for institutional strengthening of the Ombudsman, expanding his powers, increasing the responsibility of government agencies for the implementation of recommendations and developing mechanisms for interdepartmental interaction. The importance of the Ombudsman as an effective tool for the protection of human rights and the formation of a rule-of-law state is substantiated.
Keywords: ombudsman; human rights; protection of citizens’ rights; citizens’ appeals; state bodies; rule of law; recommendations of the Ombudsman; restoration of violated rights; administrative practice; judicial protection.